Optimization of the ultra-flattened normal dispersion in photonic crystal fibers infiltrated with olive oil for supercontinuum generation - Le, Hieu Van; Van, Bien Chu; Bui, Dinh Thuan; Canh, Trung Le; Dinh, Quang Ho; Van, Dinh Nguyen Van Nguyen (Photonics Letters of Poland, 2021)
This paper proposes a pure silica photonic crystal fiber (PCF), having its core infiltrated with olive oil, which allows achieving an ultra-ﬂattened normal dispersion regime. As a result, the optimization processes allows us to achieve an ultra-ﬂat normal dispersion in the range of over 682 nm within the wavelength range from 1446 to 2128 nm. Besides, the nonlinear coefficient of the selected PCF structure is extremely high (9.54 x 109 W-1.km-1 at 1550 nm). The proposed PCF structure could be very helpful in investigating the supercontinuum generation which has many potential applications in various promising areas such as spectroscopy, medical diagnostics, etc. Full Text: PDF References J.M.Dudley, G.Genty and S.Coen, "Supercontinuum generation in photonic crystal fiber", Rev. Mod. Phys. 78(2006). CrossRef T.Udem, R.Holzwarth and T.W.Hänsch, "Optical frequency metrology", Nature 416 233-7(2002). CrossRef S.Moon and D.Y.Kim, "Ultra-high-speed optical coherence tomography with a stretched pulse supercontinuum source", Opt. Express 14 11575-84 (2006). CrossRef G.P.Agrawal. "Chapter 11 - Highly Nonlinear Fibers", Nonlinear Fiber Optics (Oxford: Academic Press 2013) CrossRef V.R.K. Kumar, A.K. George, J.C. Knight, P.S.J. Russell, "Tellurite photonic crystal fiber", Opt. Exp. 11 2641-2645 (2003). CrossRef R. Buczynski, H. T. Bookey, D. Pysz, R. Stepien, I. Kujawa, J. E. McCarthy, A. J. Waddie, A. K. Kar and M. R. Taghizadeh, "Supercontinuum generation up to 2.5 μm in photonic crystal fiber made of lead-bismuth-galate glass", Laser Phys. Lett.7 666-72 (2010). CrossRef F.G.Omenetto, N.A.Wolchover, M.R. Wehner, M. Ross, A. Efimov, A.J. Taylor, V.V.R.K. Kumar, A.K. George, J.C. Knight, N.Y. Joly, P.St.J. Russell, "Spectrally smooth supercontinuum from 350 nm to 3 µm in sub-centimeter lengths of soft-glass photonic crystal fibers.", Opt. Express 14 4928-4934 (2010). CrossRef H. L.Van, V. C. Long, H. T. Nguyen, A. M. Nguyen, R. Buczyński, R. Kasztelanic, "Application of ethanol infiltration for ultra-flattened normal dispersion in fused silica photonic crystal fibers", Laser Physics, 28 115106 (2018). CrossRef J. Pniewski, T. Stefaniuk, H. L. Van, V. C. Long, L. C. Van, R. Kasztelanic, G. Stępniewski, A. Ramaniuk, M. Trippenbach, and R. Buczynski, "Dispersion engineering in nonlinear soft glass photonic crystal fibers infiltrated with liquids", Appl. Opt. 55, 5033-5040(2016). CrossRef H. D. Quang, J. Pniewski, H. L.Van, R. Aleksandr. V. C. Long, B. Krzysztof, D. X. Khoa, K. Mariusz, and R. Buczynski, "Optimization of optical properties of photonic crystal fibers infiltrated with carbon tetrachloride for supercontinuum generation with subnanojoule femtosecond pulses", Applied Optics, Vol. 57, No. 15, 1559-128X (2018). CrossRef M.Chemnitz,M.Gebhardt, C.Gaida, F.Stutzki, J.Kobelke, J.Limpert, A.Tünnermann and M.A. Schmidt, "Hybrid soliton dynamics in liquid-core fibres", Nat. Commun. 8 42 (2017). CrossRef S.Kedenburg, A.Steinmann, R.Hegenbarth, T.Steinle and H.Giessen, "Nonlinear refractive indices of nonlinear liquids: wavelength dependence and influence of retarded response", Appl. Phys. B 117 803-16 (2014). CrossRef E.Sani and A.Dell’Oro, "Spectral optical constants of ethanol and isopropanol from ultraviolet to far infrared", Opt. Mater. 60 137-41 (2016). CrossRef S.T. Wu, "Absorption measurements of liquid crystals in the ultraviolet, visible, and infrared", J. Appl. Phys. 84 4462-4465 (1998). CrossRef Z. Mousavi, B. Ghafary, M.H. Majles Ara, "Fifth- and third- order nonlinear optical responses of olive oil blended with natural turmeric dye using z-scan technique", Journal of Molecular Liquids, https://doi.org/10.1016/j.molliq.2019.04.077 CrossRef Web page: Refractive Index Info: https://refractiveindex.info. CrossRef I. Bodurov, I. Vlaeva, M. Marudova, T. Yovcheva, K. Nikolova, T. Eftimov, V. Plachkova, "Detection of adulteration in olive oils using optical and thermal methods", Bulgarian Chemical Communications, Volume 45, Special Issue B (pp. 81-85) (2013) DirectLink